Szkolenia jako czynnik rozwoju zawodowego osób z niepełnosprawnościami w świecie VUCA - Wykin, Anisa (Życie z niepełnosprawnością w świecie VUCA, 2022)
In every society there is a certain percentage of people who, due to hereditary and inborn factors, as well as diseases, accidents or abnormal living conditions, do not have full physical or mental fitness. Understanding the essence of disability is the basis for the proper use of the potential of disabled employees. The career path of these people is determined by various external and internal factors, as well as individual factors. The processes of training and professional development, understood as a set of activities consisting in the development and expansion of professional competences in order to ensure more effective performance of tasks at current and future positions, play a special role here. Training plays a very important role in the times of the knowledge economy, especially in the VUCA world, where everything is constantly changing, the conditions in which companies operate are uncertain and complex, and the excess of information causes ambiguity of the situation. The presented article deals with the subject of the effectiveness of vocational training conducted for people with physical disabilities and indicates suggestions for improving the training process, which is particularly important in the VUCA world.